THE TEACHING AND LEARNING MODELS APPLIED BY THE ENGLISH TEACHER IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Tri Gustinah; Endang Susilawati; Yanti Sri Rezeki (Universitas Tanjungpura, 2022)
The purpose of this study is to describe teaching and learning models applied by the teacher in EFL teaching. The researcher conducted a descriptive study in SMP Negeri 1 Sungai Raya, Kubu Raya by involving an English teacher. In collecting research data, classroom observation and interview were conducted to identify teaching and learning models. The result revealed that teaching and learning model the teacher used were Discovery Learning and Inquiry-Based Learning. The teacher did not follow the model steps consistently but the teacher still followed the Scientific Approach. The teacher applied the teaching and learning models to help the students to become more active during the learning process and it had been proven that these activities could help teacher and students in EFL teaching and learning.